In Vitro Cytotoxicity Test of Red Okra (Abelmoschus esculentus) Fruit Ethanolic Extract on HeLa Cells - Agung Budianto Achmad (Journal of Applied Veterinary Science And Technology, 2022)
Background: Cancer is one of the leading causes of death in pets. Among various therapeutic methods, chemotherapy is still the main choice to treat advanced and metastatic cancers. However, because of its non-target-specific mode of action, chemotherapy often causes severe side effects in patients. Purposes: This study aimed to analyze the cytotoxic effect of red okra fruit extract (Abelmoschus esculentus) on HeLa cells with a comparison of several incubation periods of therapy. Methods: Red okra fruit was extracted by the maceration method using 96% ethanol. Then its cytotoxic potency was tested in vitro on HeLa cells based on the MTT tetrazolium reduction assay. Results: The results of the MTT test showed a decrease in the viability of HeLa cells along with an increase in the concentration of red okra extract (400, 800, dan 1,600 ppm), where the highest percentage of cell inhibition was obtained at a concentration of 1,600 ppm for each group of 24, 48, and 72 hours of therapy. The lowest IC50 value was obtained by the 48-hour therapy group, which was 631.78 ppm, indicating the optimal duration of therapy of red okra against HeLa cells. Conclusion: The ethanolic extract of red okra (Abelmoschus esculentus) has an anticancer effect by inhibiting the growth and proliferation of HeLa cells. Thus, red okra fruit has potential benefits in the management of animals diagnosed with cancer.